Fifty years of the International Convention on the Elimination of All Forms of Racial Discrimination : a living instrument - Keane, David, 1978-; Waughray, Annapurna, 1960- (Manchester : Manchester University Press, 2018)
This is an edited collection on ICERD, the oldest of the UN human rights treaties. It provides a unique combination of members of the Committee on the Elimination of Racial Discrimination (CERD) and academic and other experts, to discuss the importance of the treaty on its 50th anniversary.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 12, 2018).
Keywords: Internation Convention on the Elimination of All Forms of Racial Discrimination (1965 December 21) -- History; Racism -- Prevention -- History; Law; Social discrimination & equal treatment; Social groups; Ethnic studies; Ethnic minorities & multicultural studies; Human rights, civil rights